PREVALENCE OF POULTRY COCCIDIOSIS IN AND AROUND BAHIR DAR, ETHIOPIA. - Getnet, Tegbar; Alemayhu, Tehetna; Hagos, Yohannes (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
: A cross sectional study was conducted in and around Bahir Dar with theobjective of determining prevalence of poultry coccidiosis in local strain and whiteleghorn breed chicken that are kept under free range and deep litter management systems,respectively. Flotation technique was employed to harvest coccidial oocysts from thesampled chicken faces. Out of a total of 400 chickens examined during the study period248 (60.6%) were found to be positive for coccidial oocysts. According to breeddistribution out of 200 each fecal samples from white leghorn and local strain chickens69.04 % and 51.7 % were positive, respectively. Regarding, the management systemcoccidial infection was significantly higher (X2= 12.795; P=0.000) in deep littermanagement system 145 (69.04%) when compare to free range management system103(51.7%). Prevalence of coccidiosis according to different age groups indicated thatsignificantly higher prevalence rate of coccidiosis (X2 =28.287; P=0.000) were registeredin young chicken when compare to their older counter parts. However, significantvariation was not noticed in different sex groups of chickens (X2= 1.367; P=0.242).Generally the present study showed that coccidiosis is an important parasitic disease inthe study area and further studies using large sample size should be undertaken so as toget the overall picture of the disease in the area.